4 nm ZnO nanocrystals fabrication through electron beam irradiation on the surface of a ZnO nanoneedle formed by thermal annealing. Issue 1 (2nd December 2016) - Li, Jian-Min
Abstract : The electron beam irradiation effect was explored for the integration of well-separated ZnO nanocrystal homoepitaxial growth on the surface of an individual ZnO nanoneedle. Abstract : A vertically-oriented growth of the monolithic ZnO nanocrystals (NCs)-on-nanoneedle (NN) single-crystalline (SC) hybrids is presented with intrinsic nanoscale complexity, consisting of spatially homogeneously distributed ultrahigh-density (2.0 × 10 4 μm −2 ) on-site homoepitaxial growth of 4 nm ZnO NCs on the surface of vertically oriented high-density (8 × 10 8 cm −2 ) SC [101̄0] ZnO NNs. The electron-beam stimulated "self-additive on-surface oxidation-limited growth" at room temperature is proposed for the on-site growth of numerous ZnO NCs on the (0001) facets of a single ZnO NN. Compared with heterojunctions, the unprecedented compact monolithic ZnO NCs-on-NN SC hybrids, growing from the inside out, may hold great promise for enhanced photovoltaic performance ( e.g., electron mobility) of ZnO NC-sensitized solar cells.